Modulation of cytokine levels in ameliorative effects of pulsed magnetic field on an experimental model of Chronic Constriction Injury. (July 2015) - Mert, Tufan; Altun, İdiris; Celik, Ahmet; Sürer, Tuba; Gunay, Ismail
Abstract Purpose: Clinical chronic neuropathic pain is often resistant to currently used pharmacotherapeutic applications. A number studies have shown that pulsed magnetic field (PMF) application may ameliorate the pain associated with damages, surgeries or diseases. However, possible potential mechanisms of PMF treatments have not been well documented. This study aimed to assess the therapeutic effects of PMF treatment on a Chronic Constriction Injury model (CCI) which mimics clinical chronic neuropathic pain symptoms. Materials and methods: Effects of PMF treatments or sham PMF (SPMF) were investigated by measuring the latencies, thresholds and cytokine levels (interleukin [IL]-1 beta, IL-6 and IL-10) of sciatic nerve in CCI or sham surgery rats. PMF was treated on CCI rats before (a day after surgery, PMF-AD) and after (a week after surgery, PMF-AW) the development of pain signs. Results: Rats exhibited hyperalgesia and allodynia within one week following surgery, and lasted through the experiment. PMF treatments, but not SPMF, significantly enhanced the latency and threshold. Both anti-hyperalgesic and anti-allodynic actions of PMF-AD were greater than those of PMF-AW treatment. Similarly, PMF-AD had more pronounced effects on the level of pro- and anti-inflammatory cytokines than did PMF-AW. Conclusions: The present findings may suggest that PMF treatment may reverse the CCI-induced changes in neuropathic pain behaviors by decreasing the production of pro-inflammatory cytokines and increasing the anti-inflammatory cytokine production at the site of injury.